Isolation of a soluble and template-dependent poliovirus RNA polymerase that copies virion RNA in vitro. - Flanegan, J B (1979)
A soluble RNA-dependent RNA polymerase was isolated from poliovirus-infected HeLa cells and was shown to copy poliovirus RNA in vitro. The enzyme was purified from a 200,000-X-g supernatant of a cytoplasmic extract of infected cells. The activity of the enzyme was measured throughout the purification by using a polyadenylic acid template and oligouridylic acid primer. The enzyme was partially purified by ammonium sulfate precipitation, glycerol gradient centrifugation, and phosphocellulose chromatography. The polymerase precipitated in a 35% saturated solution of ammonium sulfate, sedimented at about 7S on a glycerol gradient, and eluted from phosphocellulose with 0.15 M KC1. The polymerase was purified about 40-fold and was shown to be totally dependent on exogenous RNA for activity and relatively free of contaminating nuclease. The partially purified polymerase was able to use purified polio virion RNA as well as a template. Under the reaction conditions used, the polymerase required an oligouridylic acid primer and all four ribonucleside triphosphates for activity. The optimum ratio of oligouridylic acid molecules to poliovirus RNA molecules for priming activity was about 16:1. A nearest-neighbor analysis of the in vitro RNA product shows it to be heteropolymeric. Annealing the in vitro product with poliovirus RNA product shows it to be heteropolymeric. Annealing the in vitro product with poliovirus RNA rendered it resistant to RNase digestion, thus suggesting that the product RNA was complementary to the virion RNA template.